As you wish : inconceivable tales from the making of The princess bride - Elwes, Cary, 1962- (Touchstone, 2014)
From actor Cary Elwes, who played the iconic role of Westley in The Princess Bride, comes a first-person account and behind-the-scenes look at the making of the cult classic film filled with never-before-told stories, exclusive photographs, and interviews with costars Robin Wright, Wallace Shawn, Billy Crystal, Christopher Guest, and Mandy Patinkin, as well as author and screenwriter William Goldman, producer Norman Lear, and director Rob Reiner.